2019
DOI: 10.1080/15592324.2019.1699265
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide miRNA identification of Bacopa monnieri: a cross-kingdom approach

Abstract: Bacopa monnieri known as 'Brahmi' is a well-known medicinal plant belonging to Scrophulariaceae family for its nootropic properties. To the best of our knowledge, no characterization data is available on the potential role of micro RNAs (miRNAs) from this plant till date. We present here the first report of computational characterizations of miRNAs from B. monnieri. Owing to the high conservation of miRNAs in nature, new and potential miRNAs can be identified in plants using in silico techniques. Using the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 46 publications
(51 reference statements)
2
9
0
Order By: Relevance
“…1). Characteristics of all the predicted potential miRNAs were found to be in compliance with secondary structure prediction norms (Gadhavi et al 2019). It has been reported that a plant derived miRNAs regulate host gene expression by binding to complementary mRNAs.…”
Section: Identi Cation and Characterization Of A Paniculata Mirnassupporting
confidence: 56%
“…1). Characteristics of all the predicted potential miRNAs were found to be in compliance with secondary structure prediction norms (Gadhavi et al 2019). It has been reported that a plant derived miRNAs regulate host gene expression by binding to complementary mRNAs.…”
Section: Identi Cation and Characterization Of A Paniculata Mirnassupporting
confidence: 56%
“…Identifying mammalian gene targets in a timely manner by plant miRNA offers a reliable, effective and economical way to determine the possible effects of interactions given by exogenous molecules, regardless of their origin, on human mRNA [ [ [9] , [10] , [11] , [12] , [13] , [14] ]].…”
Section: Introductionmentioning
confidence: 99%
“…The resulted hits with a minimum of two substitutions (including gap and mismatches) on the genomic region were fetched together with their flanking region up to 350 bases. An in-house Perl script automation utilizing mfold (standalone version 3.6) [ 31 ] and VARNA [ 32 ] was applied on these captured regions, which retrieved the predicted RNA secondary structures that fulfilled the following criteria [ [33] , [34] , [35] , [36] , [37] ] including i. The miRNA sequences with breaks or loops were circumvented, ii.…”
Section: Methodsmentioning
confidence: 99%